Do Chief Executives Matter in Corporate Financial and Social Responsibility Performance Nexus? A dynamic Model Analysis of Chinese Firms - Zahid, R. M. Ammar; Khurshid, Muzammil; Khan, Wajid (Frontiers in Psychology, 2022)
This study examined the relationship between Corporate Financial Performance (CFP) and Corporate Social Responsibility Performance (CSRP). Furthermore, it explored the effectiveness of Chief executive characteristics as a moderator in the CFP-CSRP nexus. We employed a dynamic sysGMM regression model on 2439 firm-year observations of Chinese firms. The results reveal that CFP (market-based) has a significant positive impact on CSRP. However, CFP (historical) is significantly negatively related to CSRP. Furthermore, the study found that CEO turnover and CEO duality negatively moderate the CFP-CSRP relationship while CEO as CFO positively moderates this relationship. The findings have substantial implications for all stakeholders, including investors, CEOs, corporate regulators and policymakers.